Some views of health professionals and basic health care unit users concerning nutritional education - DOI: 10.3395/reciis.v1i2.86en - Wanessa Françoise da Silva Aquino; Soraia Augusta da Silva Campos; Denise de Castro Barbosa Friedrich (RECIIS, 2007)
Nutritional education is a participatory process of knowledge acquisition concerning a healthy diet. The implementation of nutritional education in the public health care system is put into question based on a survey carried out with health professionals, and with users of one Basic Health Care Unit (UBS). The execution of nutritional education requires health professional specific knowledge in order to approach alimentary problems. The nutritionist is not duly involved in the public health care. Based on quantitative and qualitative methodologies, eight UBS health professionals were interviewed in order to verify their professional and personal experiences concerning nutritional education. There were 306 users interviewed, which is a representative sample of the population which is assisted by the UBS, in order to analyze the influence of such activity in their health. The interview results show that the professionals have some difficulty in approaching information concerning alimentation and that they believe there is some room for a nutritionist's participation in a multi-disciplinary team. Around 97% of the users believe that nutrition interferes in their life quality and 19.28% of them believe that nutrition problems are related to education. Nutritional education, as a structured program, does not exist. The mobilization of nutritionists in the exercise of their function and in meeting demands of health professionals and health care users is necessary.